Effect of Chitosan Hydrogel inclusion on Centesimal Composition of Pangasius (Pangasianodon hypophthalmus) (Sauvage, 1878) Emulsion Sausages under Refrigerated Storage - Chattopadhyay, Kasturi; Martin Xavier, K. A.; Layana, P.; Balange, A. K.; Nayak, B. B. (Fishery Technology, 2020)
Chitosan is a diverse polymer of biological origin having a widespread application in food industry. The cross linking properties of chitosan beneficially affects the protein-carbohydrate interactions which in turn enhances the functional properties in emulsion based meat products. In this context, the present study was conducted to incorporate chitosan hydrogel in varying ratio (0, 0.125, 0.25, 0.375 and 0.5%) into fish mince (Pangasianodon hypophthalmus) (Sauvage, 1878) sausages in order to develop a functional sausage products upon storage. Samples without chitosan additions showed a significant and rapid decline in the crude protein content after the 24th day of storage in contrast to the chitosan treated groups where a slower rate of decline was found only after 48th days of storage. Fat content also showed greater stability in the values in case of chitosan added samples upto 48th days of storage in comparison to the control samples where a rapid decrease in the contents were observed. However, ash and carbohydrate content showed minor variations among the treatment and control groups though all were showing decreasing trend upon storage. The comparative analysis of centisimal composition of the produced sausages showed that inclusion of chitosan gel had a significant effect (p<0.05) on the keeping quality of the product when compared with control and can be presumed as a superior ready-to eat quality product.